1991
DOI: 10.2307/3869212
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cis-Acting Sequences Regulating Root-Specific Gene Expression in Tobacco

Abstract: The expression of the tobacco root-specific gene TobRB7 was characterized. Gel blot hybridizations to RNA isolated from various tobacco tissues demonstrated that steady-state TobRB7 mRNA is not detected in expanded leaf, stem, or shoot apex tissue. To determine the spatial pattern of expression, in situ hybridization to root sections revealed that TobRB7 expression is localized to root meristem and immature central cylinder regions. The 5' flanking region of the gene was studied with respect to its ability to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
1

Year Published

1992
1992
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 0 publications
1
63
1
Order By: Relevance
“…Root-specific Nematode-resistant tobacco (Yamamoto et al 1991;Ravichandra 2014) In recent years, there has been a tendency to select and verify putative unknown regulatory sequences in order to use them in synthetic constructs. Comparative studies reported several times higher expression of the mentioned before complete cassettes Pcec in comparison to the wellknown strong promoter CaMV 35S (Koul et al 2012).…”
Section: Phaseolus Vulgarismentioning
confidence: 99%
“…Root-specific Nematode-resistant tobacco (Yamamoto et al 1991;Ravichandra 2014) In recent years, there has been a tendency to select and verify putative unknown regulatory sequences in order to use them in synthetic constructs. Comparative studies reported several times higher expression of the mentioned before complete cassettes Pcec in comparison to the wellknown strong promoter CaMV 35S (Koul et al 2012).…”
Section: Phaseolus Vulgarismentioning
confidence: 99%
“…To this end, a GUS-SPA1 fusion protein was expressed under the control of tissue-specific promoters. Promoters used were pSUC2 for phloem-specificity (Stadler and Sauer, 1996;Truernit and Sauer, 1995), pCAB3 for mesophyll-specificity (Susek et al, 1993), pML1 and pCER6 for epidermis specificity (Hooker et al, 2002;Lu et al, 1996;Sessions et al, 1999), pKNAT1 for shoot meristem specificity (Lincoln et al, 1994) and pTobRB7 for root specificity (Yamamoto et al, 1991). Previously, these promoters have successfully been used to study photoperiodic flowering Endo et al, 2007), seedling development (Endo et al, 2007;Savaldi-Goldstein et al, 2007;Warnasooriya and Montgomery, 2009) and other phenotypes such as shoot branching (Booker et al, 2003).…”
Section: Research Articlementioning
confidence: 99%
“…To minimize the negative effect of the CaMV35S promoter on plant growth and development, an inducible promoter system was developed, where expression is induced after treatment with specific chemicals, such as dexamethasone (DEX), ethanol, and estradiol (Zuo et al 2000;Wang et al 2007;Andrianov et al 2010). Tissue-specific promoters, such as leaf-, phloem-, root-, fruit-, pollen-, flowerand green tissue-specific promoters, have also been used for such purposes (van Tunen et al 1988;Pear et al 1989;Yamamoto et al 1991;Rogers et al 2001;Husebye et al 2002;Gowik et al 2004;Bakhsh et al 2011). In particular, several seed-specific promoters, including Napin, USP, FAE1, oleosin, and SeFAD2 have been widely used to modify seed oil composition and content (Josefsson et al 1987;Rossak et al 2001;Suh et al 2002;Schmid et al 2005;Kim et al 2006;.…”
Section: Introductionmentioning
confidence: 99%